The Critical Point in Art. (Tokyo : Muramatsu Gallery, 1985)
Arase, Kagetoshi ; Ishihara, Tomoaki ; Ushijima, Tomoko ; Okamoto, Yakihisa ; Kasahara, Takeshi ; Kawashima, Kiyoshi ; Kikuchi, Akehiko ; Koizumi, Toshimi ; Kondo, Katsuyoshi ; Sugano, Yumiko ; etc.
The Critical Point in Art, Muramatsu Gallery, Tokyo, 1985-07-08 / 1985-08-10
English-Japanese
kunstcatalogus